PELATIHAN PENGGUNAAN APLIKASI PENGELOLAAN KEUANGAN DI UTARAKAN COFFEE - Sari, Tridarma Rosmala; Aini, kholisyatul Lisya; Lubis, Adika Saputra (COMMENT: Journal of Community Empowerment, 2023)
Utarakan Coffee and House faces challenges in financial management and increasingly fierce competition in the coffee industry. Utarakan Coffee and Shop still uses manual recording in its financial management. Financial management using manual recording can result in quite a long time to complete bookkeeping and allows many recording activities to be lost making them ineffective. Therefore, management training is needed to utilize the latest technology to improve financial management. Financial management training is carried out for all Utarakan Coffee employees by implementing the smart cashier application. The results of the financial management training show that financial application training has a positive impact on the operational efficiency of Utarakan Coffee and House, namely in the form of an increase in the accuracy of financial recording and employee understanding of digital financial tools. The results of this training show that Utarakan Coffee and House has been able to develop skills in using smart cashier financial applications to manage transactions, stock, and finances. Apart from that, Utarakan Coffee and House also uses smart application features to monitor performance and overcome obstacles in the financial management process.